Leaving the table: Organisational (in)justice and the relationship with police officer retention - Tyson, Jemma (Criminology & criminal justice, 2025)
Policing has been beset by controversy in recent years predominantly concerning issues of justice, fairness and trust including widespread concerns over police misconduct. Alongside the continued fallout of budgetary controls and a global pandemic, policing in England and Wales is facing another growing problem – police officer retention. This article takes the conceptual framework of organisational justice, incorporating both distributive and procedural elements, to qualitatively examine voluntary resignations from the police in England and Wales. The findings indicate that those voluntarily resigning from the police service experience a lack of voice, lack of recognition of skills and experience, and barriers to career development and progression which focus on both organisational processes and outcomes. This article significantly contributes to the scarce academic literature on organisational justice within policing organisations from a qualitative perspective and can have a direct impact on policing services in addressing the rising numbers of preventable voluntary resignations.